Analysis of Consumer Preferences in Purchasing Ambon Banana Fruit in the Tourism Area of Trawas Mojokerto - Anam, Khoirul; Ositiari, Andini; Ikka, Ni Dewi Ambal; Aditya, Dipa (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2024)
Bananas are a significant horticultural commodity in Indonesia with high socio-economic value. This study aims to identify the attributes consumers prefer when purchasing Ambon Bananas in the Trawas District's tourist area and determine which attributes consumers must consider. The research employs a descriptive method using observation, interviews, questionnaires, and purposive sampling for the location in Belik Village, Trawas District, Mojokerto Regency. The study involved 91 consumers who bought Ambon bananas, and the sampling technique used was accidental sampling. Primary and secondary data sources were utilized, and data analysis was conducted using Chi-Square and Fishbein multi-attribute analysis. The findings from Chi-Square and Fishbein analysis show that: 1. The consumer preference attribute is fruit freshness, with a Chi-Square value of 98.00, where the